Effects of CEO Identity on Non-family Managers’ Pay Dispersion in Family Firms: A Social Comparison Perspective - Zhang, Wei; Chen, Ling; Zhu, Jian-an (Frontiers in Psychology, 2021)
The fairness of compensation structure has been a prominent focus for nonfamily managers, and pay dispersion, which reflects compensation fairness, has attracted much attention of scholars. Based on social comparison theory, this study investigates factors that affect the pay dispersion between CEO and nonfamily managers. In family firms, CEO identity could be either a family or a nonfamily member, which is an important corporate governance form. On this occasion, this study provided insights on how CEO identity affect such pay dispersion, and also investigated the moderating effects of CEO tenure and institutional environment. Using the data of Chinese listed family firms from 2009 to 2015, the results show that the presence of nonfamily CEO could decrease the pay dispersion. Empirical evidence also supports that the negative relationship between CEO identity and pay dispersion weakens when CEO tenure increases and the institutional environment gets mature.